Teachers’ Strategies in Maintaining Classroom Interactions in Reading Classroom Through the Online Classroom During a Pandemic - Agustina, Erika; Herlina, Rina (Journal of English Education Program (JEEP), 2025)
This study focused on maintaining classroom interaction in teaching reading through an online classroom. Furthermore, this study is designed to investigate teachers ' experience of maintaining an interactive classroom interaction while teaching reading in an online classroom and also to find out the challenges the teachers encountered and solution to those challenges. The researcher employed a qualitative approach under a narrative inquiry to obtain the data and answer the research questions. The researcher used narrative data analysis that engages transcribing and coding stories. The researcher interpreted, coded, and summarized the gathered data from the semi-structural interview. The result showed that teachers maintained their interactive classroom interactions by adjusting lesson plans and implementing synchronous and asynchronous interactions. Most teachers utilize Google Meet, Zoom, Google Classroom, WhatsApp, and Google Forms as medias for teacher-student interaction during learning sessions. Almost all teacher encounter various challenges when it deals with teaching reading to students online. The major challenge that teachers have during teaching reading online is technical problem and students' attention spans. The strategy to overcome challenges in maintaining classroom interaction is to give more focus on and to communicate effectively with students' parents and the homeroom teacher. The researcher also suggests further researchers investigate teachers’ teaching methodology in online teaching reading.